ASSESSING ENGINEERING SURVEY COURSE OUTCOMES THROUGH GRADE DISTRIBUTION ANALYSIS - Muhammad Hafeez Osman; Mohd Khairul Azhar Ismail; Basharudin Abdul Hadi; Shahreena Melati Rhasbudin Shah; Badrul Nizam Ismail (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Engineering Survey are core courses for freshmen in engineering education and provide essential science, technology and comprehensive knowledge. The purpose of this study was to examine the relationship between grade distribution patterns and course performance in these classes from 2020-2023. Academic data analysis showed a pattern of high (A–B) grades in the early years, typically involving theoretical understanding as well as some level of practical skills and report-writing. But there is a marked movement towards weaker gradings (B- to D+) in 2023, which could be indicative of new pressures at play - perhaps down to alterations in how the course is being delivered or less practise. These findings bring home the fact that better pedagogical techniques and more hands-on experience are needed to combat these issues in order to improve the educational outcome for Engineering Survey courses.